Combined Use of Ninjin'yoeito Improves Subjective Fatigue Caused by Lenalidomide in Patients With Multiple Myeloma: A Retrospective Study - Ito, Tomoki; Konishi, Akiko; Tsubokura, Yukie; Azuma, Yoshiko; Hotta, Masaaki; Yoshimura, Hideaki; Nakanishi, Takahisa; Fujita, Shinya; Nakaya, Aya; Satake, Atsushi; Ishii, Kazuyoshi; Nomura, Shosaku (Frontiers in Nutrition, 2018)
Lenalidomide is an immunomodulating derivative of thalidomide, which shows anti-tumor activity against myeloma cells with immunomodulation including augmentation of T-cell and natural killer cell function. Continuous treatment with this agent shows better survival benefit in patients with multiple myeloma and combined lenalidomide with dexamethasone (LEN-DEX) is a standard treatment regimen. However, fatigue is a frequent symptom resulting from lenalidomide administration. This side-effect therefore reduces quality of life for elderly patients and, furthermore, is a reason for treatment discontinuation. Unfortunately, appropriate preventive countermeasures against lenalidomide-related fatigue have not been established. ninjin’yoeito is a traditional Chinese medicine made from the extracts of 12 herbal plants, which positively affects immunity and inflammation. It is used to treat fatigue, decreased appetite, anemia, and general malaise associated with malignant tumors and chemotherapy. We have previously reported that ninjin’yoeito significantly improved patients’ subjective fatigue symptoms treated with melphalan-prednisone for multiple myeloma. In the present study, we assessed the benefits of ninjin’yoeito as a supplementary treatment for patients with myeloma, and its effect on lenalidomide treatment regime compliance. We retrospectively analyzed 36 cases of newly diagnosed or relapsed/refractory multiple myeloma. The study included patients receiving LEN-DEX with onset of general fatigue after lenalidomide administration (13 and 23 patients with or without ninjin’yoeito, respectively). Frequency of subjective fatigue was significantly decreased in patients administered ninjin’yoeito, compared to those treated with LEN-DEX alone (92.3 % and 47.8 % of patients with and without ninjin’yoeito, respectively; p=0.008). In addition, combined use of ninjin’yoeito and LEN-DEX showed a trend towards reduced rates of treatment discontinuation (7.7 % and 34.8 % of patients with and without ninjin’yoeito, respectively; p=0.076). Our results suggest that ninjin’yoeito is an effective method for treating subjective fatigue caused by lenalidomide and may have the potential to extend lenalidomide treatment duration.